Perilaku Pemberian Kolostrum pada Bayi Baru Lahir di Wilayah Kerja Puskesmas Poasia Kota Kendari Sulawesi Tenggara - Abadi, Ellyani (Jurnal Gizi Ilmiah, 2016)
Translation types Text translation Source text 1,394 / 5,000 Translation results The indicator for giving colostrum nationally is expected to reach 80%, but in fact the provision of colostrum at the Poasia Health Center in 2014 only reached 14.4%, this is still low or not meeting the expected standards. This study aims to determine the behavior of giving colostrum to newborns in the working area of ​​the Poasia Health Center, Kendari City, Southeast Sulawesi. This type of research is analytical with a cross sectional study design. The population in the study were all mothers who had newborns at the Poasia Health Center, Kendari City, in the period of May-June 2015 as many as 54 people and a sample of 54 people who were taken by accidental sampling. The method of analysis used the chi-square test. The results of the statistical test showed that the value of p = 0.012 and = 0.430 for knowledge, p = 0.027 and = 0.471 for attitudes and p = 0.009 and = 0.661 for actions so that it can be concluded that there is a weak relationship between knowledge, attitudes and actions with giving colostrum in newborns. Suggestions in this study are in order to increase knowledge, attitudes and actions of mothers, it is hoped that the Poasia Health Center can establish policies in an effort to increase knowledge of postpartum mothers through intensive counseling or consultation activities to mothers about the importance of giving colostrum, especially to newborns.